The peridotite deformation cycle in cratons and the deep impact of subduction - Chin, Emily J.; Chilson-Parks, Benjamin; Boneh, Yuval; Hirth, Greg; Saal, Alberto E.; Hearn, B. Carter; Hauri, Erik H. (Tectonophysics, 2021)
Xenoliths play a crucial role in interpretation of mantle deformation and geochemistry. The classic work of Mercier and Nicolas (1975) introduced the concept of the peridotite deformation cycle, which connected observed microstructures to a physical sequence of deformation. We revisit Mercier and Nicolas' original concept, bringing in new constraints using large area EBSD maps and associated microstructural datasets, analysis of water contents in nominally anhydrous minerals, and trace element chemistry of pyroxenes and garnets. We apply these techniques to a well-characterized suite of peridotite xenoliths from the Eocene-age Homestead and Williams kimberlites in the northwestern Wyoming Craton. Pyroxene water content and trace element mineral chemistries reveal ubiquitous hydrous metasomatism beneath the craton, most likely linked to the Cenozoic Laramide Orogeny. Homestead xenoliths primarily exhibit coarse protogranular and equigranular textures, B-type olivine fabrics, and generally elevated mineral water contents compared to Williams. Xenoliths from Williams are strongly deformed, with porphyroclastic and transitional textures containing annealed olivine tablets, mostly A-type olivine fabrics, and generally lower mineral water contents. As a whole, mantle from Homestead to Williams reflects a cratonic scale deformation cycle that likely initiated in Laramide times and lasted until the end of orogeny in the Eocene. At Williams, evidence for a rapid deformation “sub-cycle” within the main deformation cycle is preserved in the tablet-bearing xenoliths, corresponding to the enigmatic “transitional” texture of Mercier and Nicolas (1975). Our results suggest that this texture reflects interruption of the main deformation cycle by processes possibly related to a rapidly forming lithospheric instability and generation of the kimberlite magma – offering a new interpretation of this ambiguous peridotite texture. Collectively, our results incorporate typically disparate geochemical and textural datasets on xenoliths to shed new insights into how metasomatism, volatiles, and deformation are connected in the deep cratonic lithosphere. •Peridotite deformation cycle is reexamined using EBSD, water in NAMs, and mineral chemistry.•Wyoming Craton xenoliths show trends suggesting hydrous deformation followed by rapid, dry deformation.•Transitional texture may be indicative of lithospheric instability.